(untitled) (Medico Legal Update, 2021)
In recent years, the world has experienced various medical treatments originates from the ocean, such as cytarabine, vidarabine, and ziconotide. Marine represents a great source of species with potential medical treatments due to these species’ unique properties; however, the research and discovery of this industry demand high financial resources and time management. Hence, the international government has employed intellectual property rights and patent granting as a mechanism to promote innovative research. This paper explores the benefits and disadvantages of patent granting on marine DNA discovery and application.